THE MEDIATING ROLE OF JOB SATIAFACTION ON THE RELATIONSHIP BETWEEN HR PRACTICES AND TURNOVER INTENTION - Shi, Wenquan (IJRDO - Journal of Business Management, 2022)
This paper used a qualitative research method studied the mediating role of job satisfaction on the relationship between HR practices and turnover intention of employees and studied the influences of HR Practices during the pandemic on job satisfaction and turnover intention. The results showed that job satisfaction has a significant influence on the relationship between HR practices and turnover intention. And the HR practices implemented by organizations during the pandemic have a positive effect on employee job satisfaction and a negative effect on turnover intention of employees.